2020
DOI: 10.1177/0269881120936891
|View full text |Cite
|
Sign up to set email alerts
|

Long-term administration of cariprazine increases locus coeruleus noradrenergic neurons activity and serotonin1A receptor neurotransmission in the hippocampus

Abstract: Background: Cariprazine, the novel dopamine (DA) D3-preferring D3/D2 and serotonin (5-HT)1A receptor partial agonist, has activity as an adjunctive therapy in major depressive disorder (MDD). Aims: This study aims to investigate the effects of chronic cariprazine administration in combination with the selective serotonin reuptake inhibitor escitalopram on the activity of monoaminergic systems. Methods: Rats received cariprazine alone and in adjunct to escitalopram for 2 and 14 days and the firing activity of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Pyramidal CA1/3 neurons were identified based on the following criteria: large amplitude (0.5-1.2 mV), long-duration (0.8-1.2 ms) simple action potentials alternating with complex spike discharges (Fig. 1A) (Kandel and Spencer 1961;El Mansari et al 2020). The 5-HT DRN neurons were identified by bi-or tri-phasic action potentials with a rising phase of long duration (0.8-1.2 ms) and regular firing rate of 0.5-5.0 Hz (Fig.…”
Section: In Vivo Electrophysiological Experimentsmentioning
confidence: 99%
“…Pyramidal CA1/3 neurons were identified based on the following criteria: large amplitude (0.5-1.2 mV), long-duration (0.8-1.2 ms) simple action potentials alternating with complex spike discharges (Fig. 1A) (Kandel and Spencer 1961;El Mansari et al 2020). The 5-HT DRN neurons were identified by bi-or tri-phasic action potentials with a rising phase of long duration (0.8-1.2 ms) and regular firing rate of 0.5-5.0 Hz (Fig.…”
Section: In Vivo Electrophysiological Experimentsmentioning
confidence: 99%
“…Altogether, these data imply that ketamine normalized phasic NE neuronal firing in WKY rats, and increased tonic NE transmission found in SD rats, which may underlie at least in part the rapid antidepressant action of ketamine. A similar augmentation in NE transmission is also achieved with standard antidepressant treatments, but only after chronic administration (El Mansari et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…For instance, the NE/DA releaser bupropion re-established normal firing in rats subjected to olfactory bulbectomy, which caused dampened firing activity (Dong and Blier, 2001;El Mansari et al, 2014). Normalization of 5-HT neuronal firing that is dampened following acute administration of an SSRI/ selective norepinephrine reuptake inhibitor (SNRI) was, however, observed in SD rats that received an adjunct medication such as DA/ 5-HT modulators (Seager et al, 2004;Chernoloz et al, 2009;El Mansari et al, 2020). In addition, some antidepressant strategies for MDD such as vagus nerve stimulation, agomelatine, mirtazapine, bupropion, and pramipexole all enhance the firing activity of 5-HT neurons above their baseline in naïve SD rats (Blier and El Mansari, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We had previously reported that SKF525 decreased the firing rate of 5-HT neurons of the DRN, which might result in decreased 5-HT transmission (Grinchii et al 2018). We had previously found that the increase in extracellular 5-HT, induced by the selective 5-HT reuptake inhibitor escitalopram, led to decrease in the firing rate and bursting activity of noradrenalin neurons (Dremencov et al 2007a(Dremencov et al , 2007bEl Mansari et al 2020). It is therefore possible that the enhancing effect of SKF525 on the bursting activity of noradrenalin neurons is secondary to the suppressing effect of this compound on the excitability of 5-HT neurons.…”
Section: Discussionmentioning
confidence: 99%